Cyber Attacks and Preventive Measures on Network Applications - Udoh, Godwin Joseph; Umoh, Mfreke E. (International Journal on Human-Computing Studies, 2022)
Computer network security is of great importance for many users. With the increase in network development applications, the problem of network security is becoming more and more serious. Due to the diversity of computer network connections, terminal distribution in homogeneity, network openness, and sharing of network resources, the computer network is vulnerable to different forms of attacks such as viruses, hackers, malware attacks, and other misconduct. To ensure the safety and smoothness of information, the network security and preventive measures are eyebrow nimble. This paper analyzes the following with regards to the subject matter. History of cybercrime, motives behind cybercrime, cyber-attacks. cyber-attacks prevention and the cost of not being cyber secured.